Tuning the Photo-electrochemical Performance of RuII-Sensitized Two-Dimensional MoS2 - Chen, Xin; Krajewska, Aleksandra M.; Mcguinness, Cormac; Lynes, Amy; Mcateer, David; Berner, Nina; Duesberg, Georg; Coleman, Jonathan N.; Mcdonald, Aidan R. (Chemistry - A European Journal, 2021)
Covalently tethering photosensitizers to catalytically active 1T-MoS2 surfaces holds great promise for the solar-driven hydrogen evolution reaction (HER). Herein, we report the preparation of two new RuII-complex-functionalized MoS2 hybrids [RuII(bpy)2(phen)]-MoS2 and [RuII(bpy)2(py)Cl]-MoS2. The influence of covalent functionalization of chemically exfoliated 1T-MoS2 with coordinating ligands and RuII complexes on the HER activity and photo-electrochemical performance of this dye-sensitized system was studied systematically. We find that the photo-electrochemical performance of this RuII-complex-sensitized MoS2 system is highly dependent on the surface extent of photosensitizers and the catalytic activity of functionalized MoS2. The latter was strongly affected by the number and the kind of functional groups. Our results underline the tunability of the photovoltage generation in this dye-sensitized MoS2 system by manipulation of the surface functionalities, which provides a practical guidance for smart design of future dye-sensitized MoS2 hydrogen production devices towards improved the photofuel conversion efficiency.
Created from Fastlane, Scopus look-up
Keywords: hydrogen evolution; MoS; nanomaterials; photo-electrochemistry; ruthenium